The association of lupus nephritis with adverse pregnancy outcomes among women with lupus in North America. (October 2022) - Lucas, Anika; Eudy, Amanda M; Gladman, Dafna; Petri, Michelle; Urowitz, Murray; Wyatt, Christina M; Clowse, Megan EB
Objectives: We evaluated the association of lupus nephritis (LN) and adverse pregnancy outcomes in prospective cohorts of pregnant women with SLE (systemic lupus erythematosus). Methods: We conducted a patient-level pooled analysis of data from three cohorts of pregnant women with SLE. Pooled logistic regression models were used to evaluate the association of LN and adverse pregnancy outcomes. Odds ratios and 95% confidence intervals were calculated using a fixed effect model by enrolling cohort. Results: The pooled cohort included 393 women who received care at clinics in the United States and Canada from 1995 to 2015. There were 144 (37%) women with a history of LN. Compared to women without LN, those with LN had higher odds of fetal loss (OR: 1.90; 95% CI: 1.01, 3.56) and preeclampsia (OR: 2.04; 95% CI: 1.01, 4.13). Among the 31 women with active nephritis (defined as urine protein ≥ 0.5 g/24 h) there was a higher odds of poor pregnancy outcome (OR: 3.08; 95% CI: 1.31, 7.23) and fetal loss (OR: 6.29; 95% CI: 2.52, 15.70) compared to women without LN. Conclusions: In this pooled cohort of women with SLE, a history of LN was associated with fetal loss and preeclampsia. Active nephritis was associated with poor pregnancy outcome and fetal loss.